FABRICATION AND CHARACTERIZATION OF CEFOPODOXIME PROXETIL SOLID DISPERSION FOR SOLUBILITY ENHANCEMENT (International Journal of Pharmaceutical Sciences and Drug Research, 2014)
Cefopodoxime Proxetil belongs to BCS class IV and used in treatment of upper respiratory tract and urinary tract infections. Solid dispersions (SDs) are one of the most promising strategies to improve the solubility, dissolution and ultimately oral bioavailability of such poorly water soluble drugs. The main objective of the present research was to formulate Cefopodoxime Proxetil solid dispersion employing two methods namely hot melt granulation and solvent evaporation method. The PEG 4000 and PEG 6000 were used as carrier in varied proportion (1:1, 1:2, 1:3 and 1:4 w/w). Results of FT-IR spectra revealed no potential chemical incompatibility between drug and excipients. Enhancement in the percent drug released and dissolution rate was observed in SD of PEG 6000 as to PEG 4000 and pure drug. Drug release kinetics studies revealed that the drug release from the formulations followed non-fickian diffusion and the best fitted model for drug release for Korsmeyer Peppas Model. No sharp peaks were observed in both solid dispersions (comprising PEG 4000 & PEG 6000) in PXRD spectra revealing the formation of amorphous product. Similar results were observed in DSC studies indicating disappearance of sharp fusion endothermic peak i.e. conversion of crystalline form into amorphous form. These results were further supported by SEM studies showing disappearance of crystal habit in these formulations.